Power system performance enhancement through compensation techniques - Palanichamy, Chinnasamy; Chyn, W.; Cassandra (2015)
Demands for electricity had increased tremendously over the years and subsequently power systems need to be augmented in size and performance. One possible way of enhancing the performance of power systems is through transmission lines performance upgrading. Series compensation technique is found to be very effective in heightening the power transmission line's loadability; hence it is practiced widely due to its cost effectiveness. In this research paper, a percentage compensation software package has been developed to illustrate the benefits of series compensation. This package consists of various compensation configurations such as: single capacitor configuration, twin capacitors-optimum configuration, twin capacitors-optional capacitors configuration and twin capacitors-optional placement configurations. The MATLAB GUI platform is used for the development of the software package.